Development and construction of biosensors for detection of halogenated compounds in the environment - Nevolová, Šárka, 1983- (2007)
Haloalkane dehalogenases (EC 3.8.1.5) are bacterial enzymes able to remove halogen from halogenated aliphatic compounds by a hydrolytic replacement. Halogenated compounds are dangerous for living organisms due to toxic, genotoxic and teratogenic effects. There is growing need for sensitive, rapid and in situ methods for monitoring of these hazardous pollutants. Whole-cell fiber optic biosensor for detection of 1,2 dichloroethane has been developed by Campbell et al. (2006). This project was focused on development of cell-free enzymatic fiber optic biosensor with the aim to increase selectivity and reproducibility of biosensors for detection of halogenated compounds. Fluoresceinamine based pH optode was prepared and effects of different factors, e.g. way of storage or amount of fluorescence dye, were investigated to attain stable signal. Developed pH optode provided linear response in the pH range from 3.0 to 6.6. Three different immobilization methods were tested with haloalkane deha.